2023
DOI: 10.1007/s10499-023-01076-w
|View full text |Cite
|
Sign up to set email alerts
|

Using some natural essential oils and their nano-emulsions for ammonia management, anti-stress and prevention of streptococcosis in Nile tilapia, Oreochromis niloticus

Abstract: The current study aimed to investigate the efficacy of dietary thyme essential oil (TEO), Nigella sativa essential oil (NSEO), thyme essential oil nano-emulsion (TEO-NE), and Nigella sativa essential oil nano-emulsion (NSEO-NE) in reducing total ammonia nitrogen (TAN), improving immune response, mitigating stress, and acting as anti-inflammatory agents as well as preventing streptococcosis infection in Oreochromis niloticus (O. niloticus). Fish (N = 330, 14 ± 2 g) were divided into 10 groups of 11 fish each, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that nano-emulsion of thyme essential oil can excrete anti-bacterial effects against A. hydrophila, both in vitro and in vivo in Nile tilapia, Oreochromis niloticus, concurrent with elevation of serum immunoglobulin M, lysozyme, and interleukin-1 beta (il-1b) and preventing mortality after an experimental bacterial challenge (Salam et al, 2021). Another studies revealed protection of Nile tilapia against Streptococcus iniae infection by dietary administration of nano-emulsion of thyme essential oil, which was accompanied by lower inflammation and stress (Korni et al, 2023). Hence, nanoparticle of thyme essential oil is a promising prophylactic agent against opportunistic bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that nano-emulsion of thyme essential oil can excrete anti-bacterial effects against A. hydrophila, both in vitro and in vivo in Nile tilapia, Oreochromis niloticus, concurrent with elevation of serum immunoglobulin M, lysozyme, and interleukin-1 beta (il-1b) and preventing mortality after an experimental bacterial challenge (Salam et al, 2021). Another studies revealed protection of Nile tilapia against Streptococcus iniae infection by dietary administration of nano-emulsion of thyme essential oil, which was accompanied by lower inflammation and stress (Korni et al, 2023). Hence, nanoparticle of thyme essential oil is a promising prophylactic agent against opportunistic bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%